Explorers - Healey, Tim. (Morristown, N.J. : Silver Burdett Co., 1980)
Describes the voyages of various explorers from the Phoenician circumnavigation in 600 B.C. to the Apollo 11 moon landing. A reference section provides background information on mountain climbing, overland travel, and space and underwater exploration.
Includes index.
Bibliography: p. 59.
Keywords: Explorers -- Juvenile literature; Explorers